Orthostatic Hypertension in Children: An Update - Hu, Yang; Jin, Hongfang; Du, Junbao (Frontiers in Pediatrics, 2020)
The concept of orthostatic hypertension in children was first proposed in 2012. The pathogenesis is not clear by now. Orthostatic hypertension is one of the important causes of orthostatic intolerance in children and is related to the development of essential hypertension in the future. It is commonly seen in older children, with dizziness and syncope as their main clinical manifestations. Non-drug therapy is the commonly used treatment strategy, which is effective to improve the orthostatic intolerance symptoms. In this paper, we reviewed the clinical studies on the pathogenesis, clinical characteristics, diagnostic criteria and treatment of orthostatic hypertension in children, aiming to provide new insights for the future studies on pediatric orthostatic hypertension.